The Determinants of Bank Performance in UK before and after the Vote of Brexit - XU, SHANSHAN (2019)
The study is motived by the important role of UK banking sector along with the historical event of Brexit which may bring considerably influence to UK banking sector and change the determinants of bank profitability. It aims to find determinants including internal factors and external factors that impact banks’ profits more significantly under the cloud of Brexit. Within this scope, macroeconomic data and internal data over the period of 2012 to 2018 of 53 commercial banks in UK are adopted. Through fixed effect modal and random effect model, the main findings are following, firstly, cost to income ratio has a negative relationship with ROAA, ROAE during the whole process of Brexit plus NIM in post the vote of Brexit, indicating low cost management efficiency depresses banks’ returns in nearly all aspects. Secondly, equity to total assets ratio is positive associated with ROAA all the time, ROAE in the eve of vote and NIM after the vote which means UK commercial banks in a sound and safe capital position are able to earn more than competitors. Thirdly, loan loss reserves ratio only negative impact ROAE over the period of 2012 to 2015. Then, there is an inverse association between non-interest income to operating revenues and NIM from 2012 to 2018, that is, higher non-interest incomes decrease UK banks’ net interest margins. Lastly, net loans to deposits and short-term funding ratio has a positive sign on NIM before and after the vote that increasing net loans. Accordingly, it suggests UK commercial banks focus on cost reduction, the improvement of capital strength and the calculation system of reserves. A balance between non-interest income and interest income and a trade-off between loans and profits are also necessary for them to obtain safer returns.